THE CONDITION OF CORAL REEFS IN THE WATERS AROUND THE CEMPEDAK ISLAND BINTAN REGENCY RIAU ISLANDS PROVINCE - Wenika Fitria Dona; Thamrin Thamrin; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The aim of this research is to know the condition of coral reefs including the live coral cover of the waters of Cempedak Island Bintan.This research had been conducted in the waters around Cempedak Island Bintan in May 2018.The research station is divided into 3 stations based on environmental characteristics with a depth of 5 meters.Research stations include Eagle Rock, near Jetty and Deadmans Beach. The data of coral reefs were collected by using Underwater Photograph Transect (UPT) method. Data were analyzed using Coral Point Count with Excel extension (CPCe) application.The results showed that coral cover on the study sites ranged around 23.87% to 47.87% which can be classified as poor to moderate category sequentialy.At each station can be seen a high percentage is in station III with value 47.87%, whereas at station II coral percentage is low or bad with value 23.87%.The low coral cover is caused by the strong ocean currents causing sediment staggeration so that the sediment covers the coral surface and because of the current, the number of races and dead corals found with algae to cause the coral is damaged as in station II. The quality of water such as temperature, salinity, pH and visibility of the research location was good for coral reefs recovery and growth. Keyword: Coral reef, Cempedak Island, Underwater photograph Transect (UPT), Current Speed